2-Regular Modules - AL-Mothafar, Nuhad S.; Humod, Ghaleb A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we introduced the concept of 2-pure submodules as a generalization of pure submodules, we study some of its basic properties and by using this concept we define the class of 2-regular modules, where an R-module M is called 2-regular module if every submodule is 2-pure submodule. Many results about this concept are given.